Bibliometric Analysis of Family Burden in Caring for Schizophrenic Patients: A Literature Review - Rahayu, Pratiwi; Ernawati, Ernawati; Mubin, Mohammad Fatkhul; Pranata, Satriya (GLOBAL HEALTH SCIENCE GROUP, 2024)
Research on the topic of family burden in caring for schizophrenic patients is very high. In future research studies, the researcher needs information about new innovations and trends for this topic. Objective: The purpose of this research is to explore the number of publication trends and citation trends with the highest number of publications, as well as which fields are approved for publication, network visualization, overlay visualization, and density visualization through bibliometric analysis. Method: Notes are identified through a database search https://app.dimensions.ai/, followed by a PRISMA flowchart. Publications are limited from 2019-2023, focusing on Psychology, Human Society, Health Services And Systems, and Nursing. Type of publication is article, data is analyzed using VOSviewer, then reviewed by co-occurrence and co-author. Results: Publication search with the topic of family burden in caring for schizophrenic patients produced 255.461 articles. Then screening was carried out through predetermined criteria and the results obtained became 20.370. The highest publication is in 2022, while the lowest is in 2023. Trends with this topic are stigma, information, support, knowledge, anxiety. Density visualization shows that topics with low category visualization are uncertain effects, caregivers, facilitators, distress, self stigma. The majority of researchers are in Japan and India. Conclusions: The topic of family burden in caring for schizophrenic patients should be further developed in various countries, especially Japan and India. Suggestions for future researchers are to choose a theme with a low visualization category to develop further research updates.